Vaginal mucus impedance as an aid for prediction of optimum time for breeding during estrus in cows - SHARMA, PRASHANT; TIWARl, R P; SINGH, MOHAN; SAHU, S K; YADAV, S K (The Indian Journal of Animal Reproduction, 2023)
Experiment using inravaginal probe with impedance meter was conducted to observe the pattern of vaginal mucusimpedance (VMI) during estrus. Fertility rates in cows inseminated with different hours during estrus were analysed to correlatethe VMI dring insemination with fertility. VMI during estrus was measured 6 hourly for 24 hrs in experimental cows (n=l0) withexternal signs of estrus. During estrus itself there was variation in VMI in different hours. The VMI at 0, 6, 12, 18 and 24 hrs afteronset of estrus were 41.2±0.76, 38.5±1.38, 33.7±0.83, 42.25±0.85 and 50.3±0.58 ohms respectively. The lowest VMI wasrecorded 12 hrs after onset of estrus VMI was significantly lowered from O hrs to 6 hrs (P < 0.05) and to 12 hrs (P < 0.01) whileit was significantly increased from O hr to 24 hrs after onset of estrus. Chi-square analysis of results shows significant association(P < 0.01) between VMI and non-return rates in animals (n = 56) inseminated during estrus with low impedance value (25-34ohms). There was also the significant association (P < 0.05) between VMI and pregnancy rates as detected on day 60 afterinsemination by rectal palpation.
Keywords: Cows; estrus; fertility; vaginal mucus impedance